Perception of Teaching During the Pandemic: an Ontological Perspective - Marites Antonio (Jurnal PAJAR (Pendidikan dan Pengajaran))
This study describes teachers' perception of online synchronous teaching as an alternative delivery format during the pandemic in specialized curricula in elementary schools in the Philippines. This study uses a qualitative research design and employs the case study method. The methods for gathering data are one-on-one online interviews, face-to-face focus group discussions, and analysis of classroom artifacts, which include weekly home learning plans and lesson modules. The study uses thematic analysis to analyze the data and the triangulation method to validate the generated results. The perceptions were grounded on the reported challenges and coping strategies employed by the participants in addressing the emerging gaps in education delivery during the pandemic, resulting in two major themes: views of online teaching and professional identity.Furthermore, a noticeable unfolding of teachers' professional identity during the pandemic was manifested. The results provide empirical evidence for developing teachers' professional development, well-being, teaching perception, teacher identity, and professionalism.